2010
DOI: 10.1111/j.1365-2672.2010.04738.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the sdsA alkyl sulfatase of Pseudomonas sp. ATCC19151 and its involvement in degradation of anionic surfactants

Abstract: Aims:  The presented study was aimed to reveal transcriptional regulation of genes involved in SDS degradation (sdsA and sdsB) in Pseudomonas sp. ATCC19151. In addition, the ability of Pseudomonas sp. ATCC19151 to degrade anionic surfactants present in commercial detergent and septic tank drain was analysed. Methods and Results:  Strain ATCC19151, at 30°C, degrades all SDS present in the liquid medium (up to 4% w/v of SDS) within 48 h. ATCC19151 grows in the presence up to 15% (v/v) ‘Fairy’ commercial detergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…The nucleotide sequence of two chromosomally located genes sdsA and sdsB, coding for alkylsulfatase and its transcriptional regulator respectively, were identifi ed to play signifi cant role in SDS degradation (Davison et al 1992 ). Evidence to the transcriptional regulation of sdsA gene by sdsB protein was further proved (Jovcic et al 2010 ). The ability of Pseudomonas C12 B to utilize alkyl benzene sulfonate also appears to be coded by the chromosome (Kostal et al 1998 ).…”
Section: Biological Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The nucleotide sequence of two chromosomally located genes sdsA and sdsB, coding for alkylsulfatase and its transcriptional regulator respectively, were identifi ed to play signifi cant role in SDS degradation (Davison et al 1992 ). Evidence to the transcriptional regulation of sdsA gene by sdsB protein was further proved (Jovcic et al 2010 ). The ability of Pseudomonas C12 B to utilize alkyl benzene sulfonate also appears to be coded by the chromosome (Kostal et al 1998 ).…”
Section: Biological Methodsmentioning
confidence: 96%
“…The degradation studies of SDS, LAS and three commercial laundry detergents in Chesapeake Lake revealed that they were biodegradable only with initial concentrations below 25 ppm (Cook and Goldman 1974 ). However, continuous research and optimisation of surfactant degradation has resulted in the isolation of Pseudomonas capable of removing almost up to 4 % level of SDS in 48 h (Jovcic et al 2010 ). Bacteria capable of degrading aromatic sulfonates have been isolated from industrial sewage treatment plants (Zimmermann et al 1982 ;Thurnheer et al 1990 ) or obtained through continuous adaptation (Kuhm et al 1991 ).…”
Section: Biological Methodsmentioning
confidence: 99%
“…Presence of two genes sdsA and sdsB responsible for SDS degradation in S15 plasmid was checked by PCR amplification using primers specific for sdsA gene and sdsB gene as previously described (Jovcic et al 2010). The primers were synthesized by Sigma Genosys.…”
Section: Pcr Amplification Approachmentioning
confidence: 99%
“…AE-AA 9n.d.n.a.(Ellis et al 2002)   Pseudomonas sp. AE-DA 13n.d.n.a.(Ellis et al 2002)   Pseudomonas ATCC 19151A 9n.d.n.a.(Jovcic et al 2010)   Klebsiella oxytoca A 9n.d.n.a.(Shukor et al 2009)   Comamonas sp. DSM 115091B 45–1016(Gadler and Faber 2007b)   Citrobacter braakii A 9,12n.d.n.a.(Dhouib et al 2003)   Rhizobiaceae sp.…”
Section: Search For Sulfatase Activitymentioning
confidence: 99%